SVENSSON, BERNANKE A CÍLOVÁNÍ INFLACE VE STŘEDNÍ EVROPĚ - Maršál, Aleš; Czesaný, Slavoj, 1940-; Potužák, Pavel; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2008)
This paper focuses on controversial issues of inflation targeting. The study is based on Svensson?s and Bernanke?s theory which is applied in case studies of Czech Republic, Poland and Hungary. Understanding of actual performing of inflation targeting allows us to interpret correctly econometric and statistics analysis. The object of the thesis is to decide if the central European countries should rather follow Bernanke?s or Svensson?s theoretical conclusions. Brief summary of historical development explains reasons for implementing of inflation targeting. Next, Bernanke?s and Svensson?s definition of inflation targeting is mentioned and the differences are further analyzed. In particular, the choice of price index, understanding of price stability, lags of monetary transmission mechanism, the choice between band and point target. The last part of the thesis deals with intermediate target examining the performance of central bank and market forecast.
Vedoucí práce: Slavoj Czesaný
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2008
Rok obhajoby 2008
Keywords: národní hospodářství [obor dipl. práce]; diplomové práce; master's theses